Is There Subclinical Synovitis in Early Psoriatic Arthritis? A Clinical Comparison With Gray-Scale and Power Doppler Ultrasound - Freeston, Jane E (Arthritis Care Res (Hoboken), 2014)
OBJECTIVE: Arthritis activity assessments in psoriatic arthritis (PsA) have traditionally relied on tender and swollen joint counts, but in rheumatoid arthritis, multiple studies have demonstrated subclinical inflammation using modern imaging. The aim of this study was to compare clinical examination and ultrasound (US) findings in an early PsA cohort. METHODS: Forty-nine disease-modifying antirheumatic drug–naive patients with recent-onset PsA (median disease duration 10 months) underwent gray-scale (GS) and power Doppler (PD) US of 40 joints plus tender and swollen joint counts of 68/66 joints. GS and PD were scored on a 0–3 semiquantitative scale for each joint. Clinically active joints were defined as tender and/or swollen and US active joints were defined as a GS score ≥2 and/or a PD score ≥1. RESULTS: The most common sites for subclinical synovitis were the wrist (30.6%), knee (21.4%), metatarsophalangeal (MTP) joints (26.5–33.7%), and metacarpophalangeal joints (10.2–19.4%). Excluding MTP joints and ankles, 37 (75.5%) of 49 patients had subclinical synovitis with a median of 3 (interquartile range [IQR] 1–4) joints involved. In contrast, clinical overestimation of synovitis occurred most commonly at the shoulder (38%) and ankle (28.6%). Twelve of 49 patients were classified clinically as having oligoarthritis; of these, subclinical synovitis identified 8 (75%) as having polyarthritis with an increase in their median joint count from 3 (IQR 1–4) to 6 (IQR 5–7). CONCLUSION: This study has demonstrated that subclinical synovitis, as identified by US, is very common in early PsA and led to the majority of oligoarthritis patients being reclassified as having polyarthritis. Further research is required into the relationship of such subclinical synovitis to structural progression.